Leachability and fixation of copper-chrome-arsenic (CCA) preservative from treated Malaysian hardwoods used in construction - Lai, Huat Choi (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The performance and environmental safety of CCA treated wood rely on the extent of post-treatment storage of CCA treated wood. In relation to this, a study on the comparative leachability of CCA-treated refractory and permeable heartwoods was carried out on four Malaysian hardwoods, namely Kempas (Koompassia malaccensis), Perah (Elateriospermum tapos), Acacia mangium and Rengas (Gluta spp.) Overall, this research findings may be useful as a guide for the safe application of CCA preservative and support the continue usage of the preservatives in our timber industry.